Adsorptive removal of nerve-agent simulant with zirconium-based metal-organic frameworks modified by hydrophobic monocarboxylic acids - Cho, Kyung Ho; Chitale, Sachin K.; Kim, Seung Joo; Cha, Ga Young; Hong, Do Young; Ryu, Sam Gon; Chang, Jong San; Hwang, Young Kyu (Microporous and Mesoporous Materials, 2019)
An isoreticular series of zirconium-based benzenetricarboxlyates (MOF-808)were successfully synthesized using different lengths of linear mono-carboxylic acids (i.e., formate, propionate, and valerate)as a charge-balancing ligand, and then were applied for removal of nerve-agent simulants. Removal of dimethyl methylphosphonate (DMMP)as a nerve-agent simulant of the MOF-808 analogues was conducted in dry and humid air. Tests demonstrated that the adsorption capacity of DMMP was considerably enhanced with increase in the carbon chain length of the incorporated mono-carboxylic acids of the MOF-808 (formate < propionate < valerate). The physicochemical characteristics and sorption properties of the MOF-808 analogues were thoroughly investigated using in situ FT-IR analyses and various characterization techniques, including such as XRD, N2 sorption, TGA, SEM, Elemental Analysis (EA), and hydrophobic index (HI)measurements. It is apparent that the predominant factor affecting the MOF-808 analogues for the removal of DMMP was the concentration of surface oxygenated species (μ3-OH, [sbnd]OH, or [sbnd]OH2). These could act as active sites to adsorb DMMP via hydrogen bonding with the P[dbnd]O of a DMMP molecule and then decompose it by hydrolysis. These results demonstrate that simple modulation of the surface environments of Zr-based MOFs can be adapted to tune their intrinsic efficiency for removal of toxic chemicals.
Keywords: Adsorption capacities; Characterization techniques; Dimethyl methylphosphonate; DMMP; In-situ FT-IR; Physicochemical characteristics; Surface oxygenated species; Toxic chemicals; DMMP; In situ FT-IR; Toxic chemical; Zr-based metal-organic frameworks